EVALUASI PERUBAHAN KURIKULUM 2013 KE KURIKULUM MERDEKA TERHADAP PRAKTIK PEMBELAJARAN PPKN DI SEKOLAH SMA NEGERI 1 MUARO JAMBI - Sitanggang, Putri; Heri Usmanto; Dona Sariani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The curriculum change from the 2013 Curriculum to the Independent Curriculum is one of the government's efforts to improve the quality of education in Indonesia. This study aims to assess these changes in the learning practices of Pancasila and Citizenship Education (PPKn) at SMA Negeri 1 Muaro Jambi. This curriculum change impacts the role of teachers, learning strategies, and student engagement in the learning process. This study used a qualitative approach with the CIPP (Context, Input, Process, Product) evaluation model. Data collection techniques were carried out through observation, interviews, and documentation. The research subjects consisted of PPKn teachers, the vice principal for curriculum, and students. Data analysis was conducted descriptively qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The results show that, from a contextual perspective, the implementation of the Independent Curriculum is in line with the needs of 21st-century learning. From an input perspective, teacher readiness and facilities still need to be improved. In terms of process, learning has become more flexible and student-focused, although there are still problems in developing open modules. Meanwhile, in terms of product, there has been an increase in student participation and critical thinking skills. Thus, the curriculum changes have a positive impact on PPKn learning, but there is still a need for improvement in its implementation.